Effect of solvent type on fabrication of bipolar membrane for recovering acid in BMED system - Celik, Aytekin; Hasar, Halil (Springer, 2022)
This study evaluates comprehensively the effect of chloroform (Cf) and dimethylformamide (DMfA) solvents in the fabrication of bipolar membrane on morphological structure, physical properties and electrical characteristics and presents the acid production capacity in the case of their use in bipolar membrane electrodialysis system. It was clearly showed that morphological and physical properties of BPMs were good in terms of SEM, FTIR and NMR analyses. The DMfA-based BPM exhibited the lowest resistance of 0.11 omega cm(-2), the highest water uptake capacities of 49.1%, and a maximum current efficiency of 38.1% while the Cf-based BPM performed the highest tensile strength with 1066 MPa. The results showed that DMfA-based BPMs also accomplished successfully the acid recovery due to lower electrical resistance compared to Cf-based BPMs.
Keywords: Acid recovery; Bipolar membrane; Chloroform; Dimethylformamide